Two coordination polymers as multi-responsive luminescent sensors for the detection of UO22+, Cr(vi), and the NFT antibiotic. Issue 36 (30th August 2022) - Xue, Yun-Shan; Sun, Dan-Ling; Lv, Jun-Qing; Li, Shi-Juan; Chen, Xuan-Rong; Cheng, Wei-Wei; Wu, Hong-Xiu; Wang, Jun
Abstract : Two CPs have been synthesized using solvothermal method and can act as multi-responsive luminescent probe to detect UO2 2+ cation, Cr2 O7 2− /CrO4 2− anions, and nitrofuran antibiotic in aqueous media with high sensitivity and selectivity. Abstract : Two coordination polymers, namely [Cd3 (TIYM)2 (5-SASS)2 (H2 O)2 ]·H2 O n (1 ) and [Zn2 (TIYM)(5-SASS)(μ2 -OH)]·5H2 O n (2 ), were assembled using a mixed ligand strategy with the semi-rigid linker tetrakis(imidazol-1-ylmethyl)methane (TIYM) and 5-sulfoisophthalic acid sodium salt (5-SASS). Luminescence studies reveal that compounds 1 and 2 show strong fluorescence and exhibit efficient luminescence quenching in detecting UO2 2+ cations, Cr2 O7 2− /CrO4 2− anions, and the NFT antibiotic in aqueous media, and can thus serve as promising sensors. The detection limits of compounds 1–2 are 1.96 × 10 −4 /1.36 × 10 −4 M for UO2 2+ cations, 6.53 × 10 −5 /5.41 × 10 −5 M for Cr2 O7 2− anions, 2.29 × 10 −4 /1.04 × 10 −4 M for CrO4 2− anions, and 5.62 × 10 −5 /4.74 × 10 −5 M for the NFT antibiotic, respectively, indicating that the two CPs are promising multi-functional luminescent sensors. Additionally, the possible mechanisms for luminescence quenching have been investigated using spectral overlap experiments and DFT calculations.